Penerapan Klasifikasi Massa Batuan dan Metode Kesetimbangan Batas Terhadap Kestabilan Lereng Tambang PT. Ifisdeco, Sulawesi Tenggara - Oksteming, Jenly; Awaliah, Wd Rizky; Anshari, Erwin (Universitas Halu Oleo, 2024)
PT Ifishdeco often experiences problems in its mining activities, which originate from geotechnical issues, such as landslide events. This study aims to recommend the value of slope parameters to remain stable and safe by considering the influence of geological structures and types of landslides in the South Block Jey Pit of PT Ifishdeco Tbk. Slope stability analysis using the Bishop method with Mohr-Coloumb criteria based on direct shear strength test results and rock mass classification. The results of the study show that the safety factor value of the actual slope geometry on slope A and slope B obtained safety factor values of 0.79 and 0.83 with unstable conditions caused by the influence of the presence of discontinuity planes that reduce the strength of the slope constituent. Based on the kinematic analysis results, the landslide types found on slopes A and B are classified as wedge failures. Optimization of slope geometry is required as a recommendation for slope geometry design. Optimization of the slope height and bench slope is necessary.